2018
DOI: 10.1111/bjet.12646
|View full text |Cite
|
Sign up to set email alerts
|

Autistic youth in 3D game‐based collaborative virtual learning: Associating avatar interaction patterns with embodied social presence

Abstract: This study examines interaction patterns in a series of game activities for learning social skills by autistic youth in a 3D game‐based collaborative virtual learning environment (CVLE). Researchers studying collaborative learning have indicated the importance of social interactions and social presence. However, few studies have examined the relationship of avatar social interactions with embodied social presence in a 3D game‐based CVLE. Specifically, we examined avatar‐mediated verbal and nonverbal interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…In social science topics [e.g. Zheng et al, 2009;Wang et al, 2018], the type of exercises can be categorized as role-playing and simulation of action. In Life science [e.g.…”
Section: Table 1: Teaching Methods and Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In social science topics [e.g. Zheng et al, 2009;Wang et al, 2018], the type of exercises can be categorized as role-playing and simulation of action. In Life science [e.g.…”
Section: Table 1: Teaching Methods and Theoretical Frameworkmentioning
confidence: 99%
“…Embodied cognition points out a fundamental notion that thinking is directly tied to virtual bodies when students can express their feelings and communicate a/synchronously with other peers [Zheng et al 2009;Wang et al 2018].…”
Section: Theoretical Framework and Learning Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…including in the avatar characteristics such as proximity, orientation, joint attention and gestures, achieving interactions closer to reality. Wang [48], on the other hand, presented promising results when combining verbal and non-verbal language during the interaction of avatars with people with ASD. Other authors have demonstrated the effectiveness of working with avatars in different therapeutic processes for people with ASD, functioning as tutors in the teaching of social and communication skills, as emotional regulators and in the recognition of facial expressions [20], [44], [49]- [54].…”
Section: Related Workmentioning
confidence: 99%
“…The awareness of lifelong learning has been deeply rooted in the hearts of the people. The effective flow of social resources has increased people's desire for new knowledge as China's openness continues to increase [14]. As a kind of communication learning platform, VLCs have become an important tool for knowledge construction and learning of the entire nation because they are not restricted by geographical conditions and they comprise condensed collective wisdom.…”
Section: Introductionmentioning
confidence: 99%